Molecular epidemiology of nasal isolates of methicillin-resistant Staphylococcus aureus from Jordan - Amin A. Aqel; Hamed M. Alzoubi; Anna Vickers; Bruno Pichon; Angela M. Kearns (Elsevier, 2015)
Summary: Asymptomatic carriage of methicillin-resistant Staphylococcus aureus (MRSA) can predispose the host to a wide range of infections. To inform public health strategies, this study sought to determine the prevalence and the phenotypic and genotypic characteristics of MRSA from nasal swabs of health care workers (HCWs) and other healthy individuals in Jordan. Overall, 716 nasal swabs were collected from 297 HCWs, 141 adults and 278 children in the community. MRSA was recovered from 56 (7.8%) nasal swabs, which represented carriage rates of 10.1%, 4.3% and 7.2% among HCWs, adults and children, respectively. The MRSA isolates were resistant to oxacillin (100%), erythromycin (42.8%), tetracycline (37.5%), clindamycin (5.3%), fucidin (5.3%), and ciprofloxacin (3.5%). A total of 17 different spa types belonging to eight different clonal complexes (CCs) were identified. All isolates were mecA positive, and mecC-MRSA was not detected. Analysis of the staphylococcal cassette chromosome mec (SCCmec) elements revealed that the majority (54; 96.4%) of the samples harbored the smaller type IV and V elements (the most common were SCCmec IVa or IVc, and there were two each of the IVg and V elements), and two were nontypable. The genes for Panton-Valentine leukocidin (luk-PV) were detected in 5.4% of the study isolates. A tst-positive, CC22-MRSA-SCCmecIVa clone (spa type t223) was identified as the dominant MRSA lineage among the nasal carriage isolates from both HCWs and other individuals (adults and children) in the community. These findings provide important information for public health personnel for the formulation of effective infection prevention and control strategies. Studies to further our understanding of the distribution, pathogenicity, transmissibility and fitness of this lineage would be prudent. Keywords: MRSA, Healthcare workers, Healthy individuals, SCCmecIVa